Pengaruh Hak Asasi Manusia pada Lingkungan Sekolah Dalam Perspektif Hukum - Chandra Akbar Saputra; M.Raja Parluhutan Rambe; Fauziah Lubis (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
Cases of bullying often occur and have become a common problem that occurs especially in children who are in the school environment. The school environment which is basically a place to study, a place used as a place to find friends and a place that should be a place to enjoy school days has turned into a scary, creepy and horrific place because of the many cases of human rights violations that often occur and neglected. In the school and community environment, acts or acts of bullying or psychological bullying are often found. Bullying psychologically and physically has a very bad impact on victims and even perpetrators. Therefore it is necessary to find solutions to reduce and minimize bullying so that this bullying does not happen again. In Indonesia, cases of bullying or bullying are still very high and quite worrying. In almost every school we find cases of bullying that often occur, besides that cyber bullying also occurs very often and this is outside the supervision of the school environment. In addition to providing protection and assistance to victims of bullying, one way to stop this bullying is by providing special education about the bad effects of bullying and providing education about human rights in particular and the need for strict sanctions for the behavior or actions committed by the bully. Keywords: Human Rights, Bullying, Education, School Environment